SENSITIVITAS DAN SPESIFISITAS KUESIONER RISIKO DIABETES MELITUS UNTUK METODE SKRINING DIABETES MELITUS DI INDONESIA (ANALISIS RISKESDAS TAHUN 2018) - Subawa, Ida Ayu Ketut Pujayani; Suariyani, Ni Luh Putu (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT Based on Riskesdas 2018, the prevalence of diabetes mellitus in Indonesia from 2013 to 2018 has increased from 1.5% to 2.0%. DM risk factors can be used as an effort to predict the incidence of DM in individuals through creating questionnaires. This study used a cross-sectional design using secondary data by Riskesdas 2018 with total of 24,349 samples that met the inclusion and exclusion criteria to determine the cut off point for the incidence of DM, sensitivity and specificity. Data analysis in this study used descriptive statistical analysis, bivariate, logistic regression and ROC analysis. The DM percentage is 2.11%. Several risk factors associated with the incidence of diabetes mellitus with a p-value <0.05 include age variables (aOR=3.94; 95%CI=3.10-5.02), peripheral obesity status (aOR=2.65; 95%CI=1.11–1.97), central obesity (aOR=3.22; 95% CI=1.15–1.80) physical activity (aOR=1.27; 95%CI=1.04 -1.56), non-routine consumption of anti-hypertensive drugs (aOR=1.96;95%CI=1.37-2.84), and regular consumption of drugs (aOR=2.19;95%CI=1 .63–2.95). Based on the OR value obtained, it becomes a reference for weighting in the DM risk questionnaire. Through a questionnaire prepared, the cut off for DM was obtained, namely a total score of ?10 with a sensitivity value of 84% and a specificity of 81%. Keywords: Diabetes Mellitus, Screening, Sensitivity, Specificity